African Swine Fever Diagnosis in Africa: Challenges and Opportunities - Mary-Louise Penrith; Juanita van Emmenes; Jean N. Hakizimana; Livio Heath; Tonny Kabuuka; Gerald Misinzo; Theophilus Odoom; Abel Wade; Habibata L. Zerbo; Pam D. Luka (Pathogens, 2024)
The global spread of African swine fever (ASF) in recent decades has led to the need for technological advances in sampling and diagnostic techniques. The impetus for these has been the need to enable sampling by lay persons and to obtain at least a preliminary diagnosis in the field for early control measures to be put in place before final laboratory confirmation. In rural Africa, rapid diagnosis is hampered by challenges that include lack of infrastructure as well as human and financial resources. Lack of animal health personnel, access to affordable means to transport field samples to a laboratory, and lack of laboratories with the capacity to make the diagnosis result in severe under-reporting of ASF, especially in endemic areas. This review summarizes the challenges identified in gap analyses relevant to low- and middle-income countries, with a focus on Africa, and explore the opportunities provided by recent research to improve field diagnosis and quality of diagnostic samples used. Sampling techniques include invasive sampling techniques requiring trained personnel and non-invasive sampling requiring minimal training, sampling of decomposed carcass material, and preservation of samples in situations where cold chain maintenance cannot be guaranteed. Availability and efficacy of point-of-care (POC) tests for ASF has improved considerably in recent years and their application, as well as advantages and limitations, are discussed. The adequacy of existing laboratory diagnostic capacity is evaluated and opportunities for networking amongst reference and other laboratories offering diagnostic services are discussed. Maintaining laboratory diagnostic efficiency in the absence of samples during periods of quiescence is another issue that requires attention, and the role of improved laboratory networking is emphasized. Early diagnosis of ASF is key to managing the disease spread. Therefore, the establishment of the Africa Chapter of the Global African Swine Fever Research Alliance (GARA) increases opportunities for collaboration and networking among the veterinary diagnostic laboratories in the region.